MOTOR PLASTICS AS A COMPONENT OF THE CULTURE OF MOVEMENT (EDUCATION IN THE 21ST CENTURY, 2023)
Plasticity as a qualitative and aesthetic component of movements should be considered as an important structural element of physical culture. Its formation is a necessary condition for the development of the sense of perception of the beauty of movements, formation of movement culture, which is manifested in good posture, lightness and gracefulness of movements, harmonious proportions, beautiful body in the process of physical education.The formation of plasticity of a motor action, its highest forms of aesthetics and gracefulness is nothing other than the acquisition and improvement of the motor competence of a student.Few researches dedicated to the study of movement plasticity reveal only some of its aspects.
Keywords: Keywords: plastics, culture of movement, technical skill, physical education, students.